PENGARUH LAYANAN MANAJEMEN TERHADAP KEPUASAN PESERTA DIDIK DI MAN 1 KOTA MALANG - Nurhasana, Intan (Program Studi Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2024)
This study aims to determine whether the Library Service Management variable influences student satisfaction at MAN 1 Malang City. The research method used is descriptive method with a quantitative approach, with simple linear regression data analysis techniques. The number of samples used in this study were 80 respondents, which was carried out using the Simple Random Sampling technique. The results of this study indicate that library service management has a positive effect on student satisfaction at MAN 1 Malang City. The value of the regression coefficient X is 0.376 which states that for every 1% increase in library service management, the level of student satisfaction will increase by 0.376. the regression coefficient is positive, so it can be said that the direction of the influence of the X and Y variables is positive. From the results of the t test, it can be interpreted that the library service management variable (X) has an effect on the student satisfaction variable (Y). This can also be proven by the value of tcount > ttable, which is 9.214 > 1.994.